In-depth exploration of challenges faced by women in the Turkish maritime industry: A qualitative study - Yildirim, Umut; Nart, Senem; Akar, Sevda; Sarialioğlu, Songül; Toygar, Arda; Vardar, Burak; Kaya, Sultan Çoşkun; Sari, Mustafa (SAGE Publications, 2024)
BACKGROUND: Women are underrepresented in the maritime industry compared to men. This sector continues to perpetuate gender discrimination and stereotypes, often overlooking women’s physical competence. OBJECTIVE: To explore the multi-faceted challenges faced by Turkish female officers, unveiling the different dimensions of these challenges, and providing a comprehensive understanding of their experiences. METHODS: In-depth semi-structured interviews were conducted with 40 Turkish female officers actively working on seagoing vessels. The data were analyzed using MAXQDA software. RESULTS: The challenges faced by female officers were examined using content analysis. A total of 50 different codes were identified within 10 categories. The categories are gender inequality, violence, restriction of freedom, work-family conflict, mental health, physical differences, unsafe living space, insufficient communication with management, lack of psychometric testing and limited access to health services. CONCLUSION: By shedding light on the unique obstacles faced by female officers in Turkey, this study enhances our understanding of the underlying challenges and lays the groundwork for the implementation of effective policies and practices that promote the empowerment of women in the maritime industry.
Keywords: Adult; Turkey; Sexism; Middle Aged; Interviews as Topic; Mental Health; Humans; Female; Qualitative Research; Ships; 5. Gender equality; 10. No inequality